Questionnaire on adaptation to type 1 diabetes among children and its relationship to psychological disorders - Laura Lacomba-Trejo; Selene Valero-Moreno; Sara Casaña-Granell; Vicente Javier Prado-Gascó; Marián Pérez-Marín; Inmaculada Montoya-Castilla (Universidade de São Paulo, 2018)
ABSTRACT Objective: to study the psychometric properties of an adaptive disease response questionnaire for use with Spanish children with type 1 diabetes; to analyse this response in this sample and to observe the relationship between adaptive response and levels of anxiety-depression. Method: a total of 100 patients with type 1 diabetes aged between nine and 16 years (M=12.28, SD=1.78) participated in the study, of which 59% were children. Data was collected in public hospitals via interviews using the Adaptive Disease Response Questionnaire and Anxiety and Depression Scale. The data was analysed using Pearson correlations, multiple hierarchical linear regressions, Student's t Test for independent samples, and Cohen's d effect size to determine reliability and validity. Result: the instrument was shown to have adequate psychometric properties. Adaptive response was generally high. Adaptive response is negatively related to emotional distress, being a better predictor of depression than of anxiety. There was no association betwee adaptation and sex and age. Conclusion: promoting a better adaptive response appears to reduce emotional distress, especially in the case of depression, regardless of the age or gender of the patients.